Pengembangan Media Pembelajaran Berbasis Aplikasi Game dalam Pembelajaran Bahasa Indonesia pada Siswa Kelas XI - Muhammad Aldyka Daniar; Rahmat Soe'oed; Asnan Hefni (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The aims of this study are to (1) describe the development of game media in Indonesian language learning; (2) reveal the level of interest in using game media in an effective learning process requires media in Indonesian language learning; and (3) knowing the level of effectiveness of using game media in learning Indonesian. This research is development research, with data collection steps according to the development model according to Borg & Gall. The stages taken in this research are limited to seven stages, namely research and information collecting, planning, developing the preliminary form of product, preliminary field testing, main product revision, main field testing, and operational product revision. The results of the research show that: (1) the development of learning media based on Android games with the support of the Netbeans 12.4 product oracle software; (2) students have a positive attitude towards the product by 81% in the "very interesting" category; (3) the level of effectiveness of using game media in learning Indonesian is 82% or very effective. Based on the results of these studies, it can be concluded that web-based games can be used to support learning media for high school students.